DETERMINATION OF WATER QUALITY INDEX OF GHODAZARI LAKE IN WINTER SEASON - Shagufta Anjum Abdul Haleem,; Amir A.Dhamani, (The Bioscan, 2025)
This research focuses on how environmental factors and household activities affect water quality in a specific area. Conducted over a year, the study is aimed at the assessment of the physico chemical properties and water quality index WQI of Ghodazari Lake, located in Nagbhir, Chandrapur District, during the winter season. Its objective is to evaluate the usefulne ss of the water for public use, recreational activities, and other purposes. Collection and analysis of Water samples were done over a period from September 2021 to August 2022. Then the data was processed to calculate the Water Quality Index (WQI) and the n compared with the drinking water standards recommended by the World Health Organization (WHO) and the Bureau of Indian Standards (BIS). The analysis showed that, almost all the parameters were within permissible limits. Turbidity, total dissolved solids (TDS), and electrical conductivity (EC) were found upto the acceptable A total of eleven water quality parameters was considered in the WQI approach to assess the overall groundwater quality, which resulted in a WQI value of 85. This categorizes the lake water as unsuitable for drinking purposes for both humans and domestic animals, falling into the "poor" category.The findings highlight an urgent need for proper wastewater management in the vicinity of Ghodazari Lake to improve its wa ter quality and preserve its aesthetic value. Additionally, it is recommended to plant vegetation along the lake's boundaries, which can act as a natural water purifier.